Public Health Awareness and Preparedness of Covid-19: Where are we? - Dono widiatmoko; Budi Aji; Siwi Pramatama Mars Wijayanti (Insights in Public Health Journal, 2020)
In this pandemic, we learned that prevention efforts are an important pillar of health problems, that the front line is the public health sector to prevent disease. Individual awareness to comply with health protocols is very important, to avoid increasing cases and causing the collapse of health services.